2013
DOI: 10.1111/jgs.12380
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Medication Reconciliation on Unintentional Medication Discrepancies in Acute Hospital Admissions of Elderly Adults: A Multicenter Study

Abstract: Pharmacy-based medication reconciliation leads to a substantial reduction in medication discrepancies in acutely admitted elderly adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
74
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 17 publications
3
74
0
Order By: Relevance
“…First, pharmacy technicians identified medication discrepancies in approximately 25% to 50% of patients, illustrating the widespread problem of medication history inaccuracy. 14,19,21,23,25 Second, many studies reported that it took 15 to 30 minutes per patient for pharmacy technicians to collect a medication history. 14,15,[23][24][25] This estimate is consistent with past reports, 11 further demonstrating that medication reconciliation is a resource-intensive activity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…First, pharmacy technicians identified medication discrepancies in approximately 25% to 50% of patients, illustrating the widespread problem of medication history inaccuracy. 14,19,21,23,25 Second, many studies reported that it took 15 to 30 minutes per patient for pharmacy technicians to collect a medication history. 14,15,[23][24][25] This estimate is consistent with past reports, 11 further demonstrating that medication reconciliation is a resource-intensive activity.…”
Section: Discussionmentioning
confidence: 99%
“…They were not included in this review because they focused on workflow process measures, 26 such as whether all the medications listed had a name, dose, and frequency, or contained limited information on how the quality of the pharmacy technician's work was assessed. [27][28][29] Considering all reports of pharmacy technician engagement, several best practices emerged: (a) creating a standardized process for collection of the medication history and defining a specific patient populations, 14,15,21,24,25,27,28 (b) choosing pharmacy technicians with past experience in hospital and community pharmacy settings as well as those who demonstrate good interpersonal, communication, and problem-solving skills, 16,17,25,27 (c) having pharmacy technicians who are dedicated to medication reconciliation efforts, 16,17,[27][28][29] (d) educating the hospital staff regarding the new process and how it may impact and improve their current workflows as well as patient safety, 24,28 and (e) establishing an internal training program for technicians in these roles led by pharmacists and/or experienced pharmacy technicians. Training programs generally included an education component (either didactic or through background reading and discussion), training on how to complete medication reconciliation or compile a BPMH, observation of a medication reconciliation interview completed by a pharmacist or pharmacy technician, practice or completion of a medication reconciliation interview while being observed, and finally a competency assessment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations